Business process management approach for improving agile software process and agile maturity. Issue 4 (21st December 2020) - Ozdenizci Kose, Busra
Abstract: Continuous improvement of agile software processes is inevitable in order to reach sustainable and high‐quality project outcomes. In this sense, organizations need guidance on how to apply agile software process improvement effectively; comprehensive approaches with in‐depth analysis and guidelines are required to keep software processes in balance and to continuously improve them, as in a typical business process, over time. This research aims to explore the implementation of Business Process Management approach for improving an agile software process and accordingly agile maturity level. Many organizations utilize from Business Process Management approach in order to improve workflows and to discover organization‐specific weaknesses. For this purpose, the study presents a practical, flexible model based on Business Process Management approach for agile software process improvement, which also incorporates maturity assessment for measuring the agile maturity level. Furthermore, an exploratory case study with a triangulation methodology of mixed methods was carried out for implementation of the model. The research puts forward that Business Process Management approach can be used for in‐depth analysis of agile software process, discovery of problems, and redesign of the process. The research roadmap introduces worthwhile insights on agile software process improvement for researchers and practitioners.